“Having One Child Is Selfish?”: an Analysis of Only-Child Discourse on Facebook - (:unkn) unknown (My University, 2023)
Families come in a variety of sizes, but family communication research typically represents or at least assumes families with multiple children. Although communication scholarship includes family forms beyond the traditional nuclear family (i.e., husband and wife with multiple biological children), including families who are voluntarily or involuntarily child-free, it has not included families with “just” one child. This thesis highlights the absence of communication research surrounding one-child families (OCFs). Using an interpretive, specifically discourse-dependent, lens I conducted a thematic analysis of Facebook comments in response to articles about OCFs shared by Scary Mommy. Given the absence of communication research on OCFs, this exploratory study sought to identify themes in online discourse about OCFs to help guide future research on this understudied family configuration. The findings affirmed the crossover between positive and negative stereotypes and opinions about only-children and OCFs while also producing counter-narratives. This study provides a compelling exploration of OCF discourse and future directions for family communication scholarship.
Keywords: discourse dependence; family communication; interpersonal communication; one child family; only child; only children